Delay in sexual maturation in perinatally HIV-infected youths is mediated by poor growth. (1st June 2017) - Bellavia, Andrea; Williams, Paige L.; DiMeglio, Linda A.; Hazra, Rohan; Abzug, Mark J.; Patel, Kunjal; Jacobson, Denise L.; Van Dyke, Russell B.; Geffner, Mitchell E.
Abstract : Objective: To evaluate the association between HIV infection and sexual maturation, and mediation of this association by HIV effects on growth. Design: Pooled data were analyzed from two longitudinal cohort studies, the International Maternal Pediatric Adolescent AIDS Clinical Trials P219/219C Study (1993–2007) and the Pediatric HIV/AIDS Cohort Study Adolescent Master Protocol (2007–2015), including perinatally HIV-infected (PHIV) and HIV-exposed uninfected (PHEU) youths. Methods: We evaluated age at sexual maturity among 2539 PHIV and PHEU adolescents based on annual physician-assessed pubertal staging measures. Interval-censored regression models were used to evaluate associations of HIV infection with age at maturity. Mediation analyses accounting for height and BMI Z -scores at specific ages were used to estimate direct and indirect effects of HIV infection on age at sexual maturity. Results: Mean ages at sexual maturity for PHIV girls ( n = 1032) were 15.5 years for both female breast and pubic hair and 15.9 and 15.8 years for PHIV boys ( n = 1054) for genitalia and pubic hair, respectively. PHIV youths matured approximately 6 months later on average than PHEU ( n = 221 girls and 232 boys), and this difference persisted after adjustment for race/ethnicity and birth cohort. BMI and height Z -scores mediated the association between HIV infection and later maturation in girls, accounting for up to 74% of the total HIV effect. Only height Z -scores mediated the effect of HIV on male age at maturity, accounting for up to 98% of the HIV effect. Conclusion: PHIV youths attain sexual maturity later on average than PHEU youths. Much of this difference may be attributable to deficient growth, suggesting directions for future interventions. Abstract : Supplemental Digital Content is available in the text